Accuracy and Convergence of Coupled Finite‐Volume / Monte‐Carlo Codes for Plasma Edge Simulations. Issue 6 (13th July 2016) - Ghoos, K.; Dekeyser, W.; Samaey, G.; Börner, P.; Reiter, D.; Baelmans, M.
Abstract: Present computational techniques for coupled finite‐volume/Monte‐Carlo codes for plasma edge modeling under ITER or DEMO conditions face serious challenges with respect to computational time and accuracy. In this paper, scaling laws for different error contributions are assessed and practical procedures for error estimation are proposed. First results on a 1D and a 2D test case are discussed.